2000
DOI: 10.1128/aem.66.7.2835-2841.2000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfide and Temperature on Species Composition and Community Structure of Hot Spring Microbial Mats

Abstract: In solfataric fields in southwestern Iceland, neutral and sulfide-rich hot springs are characterized by thick bacterial mats at 60 to 80°C that are white or yellow from precipitated sulfur (sulfur mats). In low-sulfide hot springs in the same area, grey or pink streamers are formed at 80 to 90°C, and a Chloroflexus mat is formed at 65 to 70°C. We have studied the microbial diversity of one sulfur mat (high-sulfide) hot spring and one Chloroflexus mat (low-sulfide) hot spring by cloning and sequencing of small-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
228
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(246 citation statements)
references
References 29 publications
(21 reference statements)
10
228
2
Order By: Relevance
“…Phylogenetic analysis indicated that strain HGMK1 T is most closely related to the uncultivated environmental clones SRI-40 (Skirnisdottir et al, 2000) and NAK-14 (Yamamoto et al, 1998), but distantly related to the cultivated strains P. guaymasensis EX-H2 T , P. marina EX-H1 T (Götz et al, 2002) and Hydrogenothermus marinus VM1 T (Stöhr et al, 2001). P. marina EX-H1 T and P. guaymasensis EX-H2 T were respectively isolated from deep-sea hydrothermal vent sulfide structures in the EPR (9uN) and the Guaymas Basin (Götz et al, 2002).…”
Section: Comparison With Related Genera and Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis indicated that strain HGMK1 T is most closely related to the uncultivated environmental clones SRI-40 (Skirnisdottir et al, 2000) and NAK-14 (Yamamoto et al, 1998), but distantly related to the cultivated strains P. guaymasensis EX-H2 T , P. marina EX-H1 T (Götz et al, 2002) and Hydrogenothermus marinus VM1 T (Stöhr et al, 2001). P. marina EX-H1 T and P. guaymasensis EX-H2 T were respectively isolated from deep-sea hydrothermal vent sulfide structures in the EPR (9uN) and the Guaymas Basin (Götz et al, 2002).…”
Section: Comparison With Related Genera and Speciesmentioning
confidence: 99%
“…The most similar rDNA sequences were those from the environmental clones SRI-40 (97?5 %) (Skirnisdottir et al, 2000) and NAK-14 (97?5 %) (Yamamoto et al, 1998), respectively obtained from Icelandic and Japanese hot spring microbial mats (Fig. 1), and from the cultivated strains Persephonella guaymasensis EX-H2 T (91?1 %) and Persephonella marina EX-H1 T (90?6 %) (Götz et al, 2002) ( Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The candidate phylum OP5 was represented originally by environmental clone sequences retrieved from the Obsidian Pool in Yellowstone National Park (Hugenholtz et al, 1998a) and indicated an independent phylum-level lineage in the domain Bacteria (Hugenholtz et al, 1998a, b;Rappé & Giovannoni, 2003). Since then, environmental clone sequences belonging to this phylum have been detected in various environments (Dojka et al, 1998;Humayoun et al, 2003;Inagaki et al, 2006;Kaksonen et al, 2004;Ley et al, 2006;Skirnisdottir et al, 2000;Teske et al, 2002). Strain AZM16c01 T was the first cultivable isolate accommodated in OP5.…”
mentioning
confidence: 99%
“…The last lineage largely consisted of a number of previously uncultivated environmental rDNA clones obtained from global terrestrial hot-spring environments such as in Yellowstone National Park (Hugenholtz et al, 1998;Reysenbach et al, 2000a), Iceland (Skirnisdottir et al, 2000;Takacs et al, 2001) and Japan (Yamamoto et al, 1998), and in subterranean hot springs (Marteinsson et al, 2001), and even in deep-sea hydrothermal vent systems (Reysenbach et al, 2000b, c). Recently, however, several representative strains of this lineage such as Hydrogenothermus (Stöhr et al, 2001), Persephonella (Reysenbach et al, 2000a;Götz et al, 2002) and a potentially new genus of strains (Takai et al, 2002) have been successfully isolated from shallow and deep marine hydrothermal vent environments and from a subsurface hot aquifer environment.…”
mentioning
confidence: 99%